The effect of substance uses on antiretroviral treatment adherence in primary health care - Ramprakash Kaswa; Marietjie R. de Villiers (South African Family Practice)
Background: Adherence to antiretroviral treatment (ART) is the primary factor determining how an individual responds to their treatment. Unfortunately, individuals who use substances experience suboptimal adherence to their treatment, but little is known about the exact effects of their use on ART adherence in primary health care settings.